Analysis of English Speaking Ability Viewed from Students' Reading Habits - Purwo Haryono (Universitas Muhammadiyah Enrekang, 2021)
This study aims to describe students' speaking English skills regarding their reading habits. The research method used in this study is a survey method. Data was collected using questionnaires and interviews. After analyzing the data using statistical methods, the research results can be described as follows. The results of the hypothesis testing indicated a beneficial relationship between reading habits and students' speaking prowess. The correlation coefficient r count of 0.739, which is higher than the r table and is represented as rxy = 0.739 > t 0.5 (1:30) = 0.349, serves as evidence for this. The findings indicate that at the t table level of 5%, 0.5 (1:28) = 2.048 when the t value is then consulted on the t value table. These findings show that the t-test is superior than the t-table. The equation of the linear regression line, which reads = 18.90 + 0.92 X, expresses the impact of the two variables. According to this equation, speaking ability (Y) increases by one unit for every rise in the reading habit variable (X) score, with a constant of 0.92.